Measuring care transitions in Sweden: validation of the care transitions measure - Flink, Maria (Int J Qual Health Care, 2018)
OBJECTIVE: To translate and assess the validity and reliability of the original American Care Transitions Measure, both the 15-item and the shortened 3-item versions, in a sample of people in transition from hospital to home within Sweden. DESIGN: Translation of survey items, evaluation of psychometric properties. SETTING: Ten surgical and medical wards at five hospitals in Sweden. PARTICIPANTS: Patients discharged from surgical and medical wards. MAIN OUTCOME MEASURE: Psychometric properties of the Swedish versions of the 15-item (CTM-15) and the 3-item (CTM-3) Care Transition Measure. RESULTS: We compared the fit of nine models among a sample of 194 Swedish patients. Cronbach’s alpha was 0.946 for CTM-15 and 0.74 for CTM-3. The model indices for CTM-15 and CTM-3 were strongly indicative of inferior goodness-of-fit between the hypothesized one-factor model and the sample data. A multidimensional three-factor model revealed a better fit compared with CTM-15 and CTM-3 one factor models. The one-factor solution, representing 4 items (CTM-4), showed an acceptable fit of the data, and was far superior to the one-factor CTM-15 and CTM-3 and the three-factor multidimensional models. The Cronbach’s alpha for CTM-4 was 0.85. CONCLUSIONS: CTM-15 with multidimensional three-factor model was a better model than both CTM-15 and CTM-3 one-factor models. CTM-4 is a valid and reliable measure of care transfer among patients in medical and surgical wards in Sweden. It seems the Swedish CTM is best represented by the short Swedish version (CTM-4) unidimensional construct.